APLIKASI TES INTELLIGENCE QUOTIENT (IQ) MENGGUNAKAN PHP DAN MYSQL (Journal of Innovation And Future Technology (IFTECH), 2019)
Intelligence Quotient is a score derived from a test tool. This study aims to create a test application intelligence quotient. The method used in this research is the literature that begins with collecting information and data relating to IQ tests, after it analyzed to find the problems and deficiencies in the IQ test. These results indicate that IQ tests manually requires a lot of equipment, such as test kits, worksheets, a measure of time and stationery. In this process if there is equipment that is experiencing a shortage or damage will be an obstacle to the implementation of the IQ test. In the manual iq test scores can not be determined quickly. With applications built an IQ test can overcome many obstacles and test equipment due to damage or lack of test equipment. With an IQ test is implemented into an application so determining IQ tests can be done quickly.